Influence of Supplementary Cementitious Materials on the Service Lifeof Concrete Structure Under Chloride Exposed Environment - Joon Shin, Kyung; Yong Kim, Yun; Seok Jang, Bong (International Journal of Engineering and Technology, 2018)
Recently, a variety of studies has been carried out to predict or design a service life of concrete. To insure a targeting service life and long-term performance of concrete structures under chloride ingress environments, mixture proportion of concrete needs to be selected properly based on knowledge about the role and performance of each constituent of mixtures. Recently, supplementary cementitious materials have been widely adapted as components of concrete mixtures due to their outstanding performance in relation to the durability. However, we donâ€™t have much information how much these materials influence the durability performance of concrete. Therefore, this study has explored the influence of supplementary cementitious materials on the service life of concrete structures.Â